(untitled) (Research, Society and Development, 2016)
This article aims to present a historical approach to the energy sector in the state of Amapa, in order to understand energetic action to interconnection to the National Interconnected System - SIN. Given this conjecture, the following question arose: How did the demand for electricity consumption in this period? The hypothesis presented indicates the population swelling as increased demand, which caused energy bottleneck by lack of investment in the sector. To answer this question, we were made bibliographic and field research and subsequent analysis for structuring data. The result points to a Federal Government initiative to encourage the interest in exploring this lot, which was supplied by auction in 2008. The winning company was the ISOLUX. With the complete interconnection; the state becomes part of the National Interconnected System, completing the Brazilian grid, which is made today by several production plants and distribution at the same time. In this scenario, the state now holds firm energy for local service, as well as export, leaving a production bottleneck situation for the expansion of energy.